若年者動脈硬化症におけるエラスターゼの分布と局在に関する研究 - 由谷 親夫; 植田 初江; 岩 信造; 田原 義孝 (動脈硬化, 1987)
In an attempt to obtain information regarding vascular elastase in children and young adults, under taken to elucidate the initial stage change in the arteries as regards atherosclerosis; we examined immunohistochemical localization of human pancreatic elastase and Apolipoprotein B on aorta in 21 patients (mean 20.9±14.8).In order to obtain the objective parameter of atherosclerosis, these aortae were studied grossly by the point counting method employing a modified Gore's score, and histologically using Imagelyzer system for medial contents of elastin, collagen and smooth muscle cells.The surface involvement and atherosclerotic index increased with age (p<0.01), and also their scores correlated to decrease of area % of elastin in media (p<0.05).Elastase was also demonstrated in intimal background and SMC which increased with age (p<0.05), and medial SMC which showed no correlation with age.Apolipoprotein B was already demonstrated in SMC of the intimal thickening of aortae which increased with age.In conclusion, elastase seems to play an important role in the development of atherosclerosis even in children and young adults.